Darwin/MP: an environment for parallel and distributed programming - Magee, J.; Kramer, J.; Dulay, N. (Hawaii International Conference on System Sciences, 1993: Proceedings, 1993)
Darwin/MP is a programming environment for distributed memory parallel computers. Programs are constructed from hierarchically structured configurations of processes. These process configurations are described explicitly in the Darwin configuration language. In addition to expressing the initial or static structure of a parallel program, Darwin can be used to express structures which change dynamically as execution progresses. Generic structures allow commonly used parallel programming paradigms to be captured as program skeletons. Processes are programmed in a conventional sequential language augmented with the MP message passing primitives. The authors illustrate program development and execution in the environment by means of a set of examples. In addition, they report on the performance of Darwin/MP programs and on experience with the use of the environment. Darwin/MP is currently targeted at developing programs for transputer based multicomputers and for workstation clusters.< >